Encyclopedia of Analytical Chemistry 2000
DOI: 10.1002/9780470027318.a6003
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Pressure Ionization Mass Spectrometry

Abstract: The atmospheric pressure ionization (API) techniques serve to transform neutral analytes into ionic species that may then be analyzed by mass spectrometry (MS). Ionization takes place under ambient pressure (∼1 atm), and formed ions are subsequently directed into the low‐pressure regions of the mass spectrometer for mass analysis. The API techniques have offered notable successes in enabling ionization of nonvolatile compounds contained in solution that are not amenable to “classical” mass spectrometric ioniza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 164 publications
0
5
0
Order By: Relevance
“…x z 2 protonated monomer analyte 2 2 proton bound dimer 2 neutral (2) While proton bound trimers can form at subambient temperatures and are observed in mobility spectra, ion lifetimes are submillisecond at or above 25 °C and are not commonly seen in applications of IMS today with 1 to 10 ms time scale. 29,30 Only reactions with hydrated protons are considered in models developed here although recent studies have demonstrated that precursor ions including O 2 + can be utilized at high electric fields and reduced pressures.…”
Section: Mh (H O) M M H (H O) Wh Omentioning
confidence: 99%
See 1 more Smart Citation
“…x z 2 protonated monomer analyte 2 2 proton bound dimer 2 neutral (2) While proton bound trimers can form at subambient temperatures and are observed in mobility spectra, ion lifetimes are submillisecond at or above 25 °C and are not commonly seen in applications of IMS today with 1 to 10 ms time scale. 29,30 Only reactions with hydrated protons are considered in models developed here although recent studies have demonstrated that precursor ions including O 2 + can be utilized at high electric fields and reduced pressures.…”
Section: Mh (H O) M M H (H O) Wh Omentioning
confidence: 99%
“…Analytical response in atmospheric pressure chemical ionization (APCI) mass spectrometry (MS) and ion mobility spectrometry (IMS) at ambient pressure , is governed by gas phase reactions between analyte neutrals and reagent ions, often derived from proton clusters in positive polarity. Such reactions occur in a significant number of ion sources for MS , including corona discharges, , electrospray ionization, dielectric barrier discharges, , and soft X-rays. One stable and reliable source at ambient pressure, the beta emitter 63 Ni, was used in early API MS instruments and can be found in IMS drift tubes in use today. , The foundations for understanding gas phase ion–molecule reactions were developed and refined by the mid-1970s with a broad experimental record for mass spectrometry including chemical ionization MS and studies with ionization detectors. These reactions as shown in eq for reactions between hydrated protons (reagent) and substances M (analyte) commonly occur at elevated or ambient pressure with ions at thermal energies.…”
Section: Introductionmentioning
confidence: 99%
“…In the positive-ion mode, proton transfer occurs from the adducts to the analyte. In the negative-ion mode, proton subtraction produces the molecular ion …”
Section: Introductionmentioning
confidence: 99%
“…In the negative-ion mode, proton subtraction produces the molecular ion. 12 The advantage of using APCI is that ionization occurs in the gaseous state than in the liquid state in ESI, which enables APCI to work with non-polar solvents. Also, APCI is less susceptible to matrix effects (including ion suppression) compared to ESI, and therefore, APCI can be considered for a wide range of applications including non-polar analytes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This produces spectra that generally contain just molecular ions with very little fragmentation, thus simplifying interpretation of datasets. 1 The technology has been applied across a wide range of disciplines and has enabled advances in areas such as drug metabolism, 2 proteomics, 3 metabolomics, 4,5 lipidomics, 6 and imaging. 7 The increasing ease of use and robustness of these once complex systems, combined with the provision of myriad software tools to confidently extract information from data, have moved this instrumentation into the hands of the bench scientist.…”
Section: Introductionmentioning
confidence: 99%